Holmium-166 Radioembolization - Lam, Marnix G. E. H.; Smits, Maarten L. J.; Bruijnen, Rutger C. G.; de Keizer, Bart; Braat, Arthur J. A. T. (Digestive Disease Interventions, 2021)
Radioembolization is usually performed with microspheres containing yttrium-90 (90Y). Holmium-166 (166Ho)-microspheres were developed as an alternative new product for radioembolization. The unique characteristics of 166Ho-microspheres allow for improved imaging possibilities. They can be visualized and quantified, already at low numbers and activities, to predict treatment distribution using 166Ho-microspheres at scout quantity during pre-treatment simulation. The option to reliably predict the distribution of microspheres provides physicians control over the treatment, allowing them to select and treat patients with a personalized treatment plan. Safety and efficacy were established in several clinical studies. 166Ho-microspheres radioembolization aims to optimize individualized treatment planning in order to improve treatment outcomes.
Keywords: radioembolization; holmium; liver